The effect of special exercises according to the work done using the force measuring platform (Foot Scan) to develop the power transmission indicator and the accuracy of the aiming from the corner area with the hand roller - Ghazi, Ghazwan Faisal; Azeez, M. DHUha Saad; Jasim, Abdul Sattar (International Journal of Psychosocial Rehabilitation, 2020)
Sports activities took another form to achieve progress and achievement, and thus work began to introduce applied sciences such as physiology, anatomy, biomechanics, kinesiology and other sciences in training operations, and correction from the corner area is one of the most difficult types of shooting with a hand ball as it requires high skill due to the narrow angle of correction and the proximity of the scoring area to The line of the field, as well as the presence of the opponent player and the goalkeeper of the opposing team, which makes accuracy the decisive factor in the success of the correction. Offensive does not depend on developing physical capabilities and skills, designing and building tests only, as well as the phenomenon of kinematic errors that accompany the performance and the indicator of energy transfer between the joints of the body. Therefore, scientific solutions should be developed through effective training methods to develop the physical and skill abilities of the players according to correct biomechanical conditions during Applying the vocabulary of the training curriculum and knowing the extent of its impact on developing a transfer index Energy as well as the accuracy of the skillful performance to shoot by jumping high to open the largest possible distance. And biomechanics helps us in the search for sports movements in terms of mechanical, anatomical, physiological and physics, drawing information from them as the link of the physical and anatomical aspects with the mechanical aspect, we can identify the best performance and the extent of the relationship of this performance in minutes Correct movement and its geometrical and temporal paths by discovering errors in the course of the movement and knowing its causes and working to avoid them and knowing the strengths and weaknesses in order to achieve the scientific foundations of the movement in an elaborate manner. The researchers agree with (Aref and Mohsen: 1989: 156-158), that correction from the corner is difficult becausethe defending player stands in front of the attacker on the goal area line, which requires the attacker to jump forward towards the line (4) m parallel to the goal line while keeping the ball. Out of reach of the defender. In this type of correction, we assume that the right player is aiming from the corner to the right. The goalkeeper is aimed at the left player from the corner to the left of the goalkeeper.